SmartASN: A Sustainable Digital Transformation to Human Resource Management in Indonesia’s Bureaucracy 4.0 - Nyeleker Kerkulah P.; Fridayani Helen Dian; Chiang Li-Chun (SHS Web of Conferences)
This article explores the impact of the SmartASN, which aims to foster technologically smart employees as digital talent and leaders, who will lead Indonesia to a world-class bureaucracy amidst the global competition sparked by the Industrial Era 4.0 demanding a smart society. The research applied a qualitative method with a case study approach, relying on secondary data collected from newspapers, journals, the SmartASN platform, etc. Using the crosstab feature, the data were interactively analysed with the NVivo 12 plus software. The theory used in this research is the Harvard Model for HRM developed by Michael Beeer. The findings indicate that the transformational impact of the SmartASN on Indonesia’s bureaucracy 4.0 can be seen mainly from HR policies, primarily, employee influence and work systems ensuring that the bureaucratic reform is compliant with relevant laws and a clear picture of the resources and capabilities required to achieve its goals. Further, these policies have resulted in HR outcomes, mainly improved employee competence and cost-effectiveness, contributing to the success of the government’s bureaucratic reform agenda. Lastly, the long-term consequences are expected to strengthen the government and employees’ effectiveness, and societal well-being creating a high-performing bureaucracy equipped to meet the challenges of the digital era.